2015
DOI: 10.1063/1.4930919
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Evidence for dipole-bound excited states in gas-phase I− ⋅ MI (M = Na, K, Cs) anionic salt microclusters

Abstract: We report the first UV laser photodissociation spectra of gas-phase I(-) ⋅ MI (M = Na, K, Cs) alkali halide anionic microclusters. The photodepletion spectra of these clusters display strong absorption bands just below the calculated vertical detachment energies, indicative of the presence of dipole-bound excited states. Photoexcitation at the peak of the transition to the dipole-bound excited state results in production of a primary [MI](-) photofragment along with a less intense I(-) ion. The photofragmentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
4
6
0
Order By: Relevance
“…and is also consistent with the fact that dipole-bound excited states can be observed via photodepletion spectroscopy in our instrument [50,51]. Our calculations indicate that the I -…”
Section: Assignment Of the I -•G Excited Statessupporting
confidence: 90%
“…and is also consistent with the fact that dipole-bound excited states can be observed via photodepletion spectroscopy in our instrument [50,51]. Our calculations indicate that the I -…”
Section: Assignment Of the I -•G Excited Statessupporting
confidence: 90%
“…Band I in the photodepletion spectrum of I -•A (Figure 4a) being accessed in this region. We have previously shown that dipole-bound excited states can be observed in our instrument following near-threshold anion excitation [27,38,39]. The identity of the shoulder peak at 4.17 eV resembles similar structures present in the nearthreshold photodepletion spectra of anionic alkali halide clusters (e.g.…”
Section: Assignment Of the Excited States Of The X -•A Clusterssupporting
confidence: 66%
“…The identity of the shoulder peak at 4.17 eV resembles similar structures present in the nearthreshold photodepletion spectra of anionic alkali halide clusters (e.g. I -NaI) [38], which were assigned to excitation of the vibrational envelope in the dipole-bound excited state of the cluster.…”
Section: Assignment Of the Excited States Of The X -•A Clusterssupporting
confidence: 62%
“…so that the 4.0 eV band for the I -•U and I -•T clusters can be confidently assigned to excitation of a dipole-bound excited state. Indeed, we have found clear evidence for the formation of dipole-bound excited states within our laser-interfaced mass spectrometry instrument following near-threshold excitation of anionic salt clusters (I -•MI where M = Na, K, Cs),44 and are therefore confident that these states can be observed using our experimental method. The absorption spectrum of the I -•C cluster in the vicinity of band I strongly resembles the absorption spectra of the I -•U and I -•T clusters, displaying a prominent absorption band in the spectral region where the VDE of the cluster is expected to occur.…”
supporting
confidence: 53%
“…We note that these excited states are resolved in the photofragment action spectra but not in the photodepletion spectra since the photodepletion spectra include spin-orbit state. 44 However, the [KI]photofragment spectrum that accompanies the photodepletion spectrum of this cluster revealed that no ionic photofragments were produced across the region of the upper spin-orbit state of the cluster. We concluded that the lack of photofragments resulted from rapid spin-orbit relaxation of the upper iodine 2 P½ state accompanied by electron detachment occurring on a timescale that is faster than decay to ionic photofragments.…”
Section: B Photodepletion Of the I -•M (M = U T C) Clustersmentioning
confidence: 93%